Determinants of Infrastructure Spending Efficiency in Indonesia: Data Envelopment Analysis (DEA) and Tobit Regression Approach - Hartono, Sri; Rahman, Aulia Fuad; Tojibussabirin, Muhammad (Journal of World Science, 2023)
This study aims to measure the efficiency value of the Ministry of PUPR's infrastructure development in each province in the 2020-2022 period and examine the influence of the determinants of efficiency through fiscal capacity, population, and area. The data used in this study uses secondary data, namely expenditure realization data in the PUPR Ministry's financial reports, Minister of Finance Regulations regarding regional fiscal capacity, and data on population and area according to the Central Bureau of Statistics. This study uses two stages of analysis; the first is to measure technical efficiency with the DEA approach through the assumption of input-oriented VRS (Variable Return to Scale), and the second is to analyze the determinants using the Tobit regression model. The study results show that the average infrastructure development efficiency score decreased over 2020-2022. Other results find that fiscal capacity has an effect on increasing the efficiency of infrastructure development, and population size and area have an effect on reducing the efficiency of infrastructure development.